Autonomous vehicles, human agency and the potential of urban life. Issue 10 (29th June 2020) - Yeo, Si Jie Ivin; Lin, Weiqiang
Abstract: Research on autonomous vehicles has hitherto been largely concerned with its technological infrastructure, and with the management of smart transport systems in urban space. While there is a growing body of work on the sociological perspectives of autonomous vehicles, it has tended to remain technocentric, focusing on how self‐driving innovations have an effect on cities and urban lives. By thinking through the notions of sensation, action, and encounter, this paper advances a reconceptualisation of autonomous vehicles that better accounts for human agency and sentience in an increasingly automated urban world. More broadly, this paper seeks to illuminate the emergent and creative potential of urban life to unsettle and complicate the taken‐for‐granted power of smart and autonomous technologies in enacting urban transformations.